Mill scale derived iron oxide nanoparticles and surface modification for wastewater treatment - Abdul Rahim @ Arifin, Azdiya Suhada (2018)
A balance ecosystem is very important to sustain livelihoods, human well-being, population of species and environment. Pollutions such as land pollution and water pollution imbalanced and disturbed the ecosystem, affected the living things in different ways. Tremendous accumulation of mill scale waste consisting of iron oxides, metal alloys and impurities such as dust and sand contributing to the land pollution whereas discharging untreated wastewater into water bodies contributing to the water pollution endanger the environmental ecosystem. To make use of the mill scale waste, iron oxide was extracted by using magnetic separation technique (MST) and Curie temperature separation technique (CTST) and recycled in wastewater treatment. However, extremely small sizes of iron oxide nanoparticles tend to agglomerate and limited the performance of iron oxide nanoparticles in wastewater treatment. Hence the surface modification of iron oxide nanoparticles with surfactant, Cetyltrimethylammonium bromide (CTAB) was needed to overcome the agglomeration problem. The extracted iron oxide was milled for 4, 6, 9 and 12 hours using High Energy Ball Milling (HEBM) machine to obtain different average particle sizes of the iron oxide nanoparticles. The morphological, physical and magnetic properties of the extracted iron oxide nanoparticles from mill scale waste before and after surface modification were studied. The performance of extracted iron oxide nanoparticles in wastewater treatment was also studied by analyzing the colour, Total Solids (TS), Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) of wastewater before and after treatment. Highly crystalline iron oxide extracted from the mill scale waste consisted of hematite, magnetite and wuestite phase which undergo phase transformation and decreasing average particle size with prolong milling time. The iron oxide nanoparticles (IONp) were agglomerated and their surface area per volume of the iron oxide nanoparticle were low. The surface modification of iron oxide nanoparticles with CTAB (IONpCTAB) were successful as HRTEM image show average coating layer of 2.7 nm on the surface of iron oxide nanoparticles. The surface modification overcome the agglomeration problem and increased the surface area per volume of the iron oxide nanoparticles but decreased the magnetic properties of iron oxide nanoparticles. The colour, total solid (TS), total dissolved solid (TDS) and total suspended solid (TSS) were greatly removed from the untreated wastewater after treated using both iron oxide nanoparticle without and with surface modification. The presence of CTAB helps in decolorized the colour of wastewater from dark brown to light yellow colour. CTAB also increased the BOD and COD values of wastewater after treated with iron oxide nanoparticles modified with CTAB. The surface area per mass of iron oxide plays important role in wastewater treatment as the performance of iron oxide nanoparticles increased with increasing surface area per mass of iron oxide nanoparticles resulted by reduction of average particle sizes of iron oxide nanoparticles.